ANALISIS EFEKTIVITAS PENGGUNAAN MULTIMEDIA PEMBELAJARAN DIGITAL DI SEKOLAH DASAR - Savitri, Nabila Defani; Putri, Peni Indriyani; Wulandari, Sri; Alpian, Yayan (Universitas Negeri Medan, 2024)
Abstract: This research on analysis of the use of learning multimedia aims to find out the extent to which schools implement and know about digitalization in schools. By introducing digital media to schools from elementary school level, it will also have a good impact on students' development in their efforts to utilize technology in the future. The research method used in this research is a qualitative descriptive method with interview techniques and questionnaires filled in by students regarding the use of digital learning media in their school. And the factors causing the ineffective use of digital multimedia at SDN Nagasari 4 are influenced by several external and internal factors.Keyword: multimedia, digital media, learning Abstrak: Penelitian tentang analisis pengguanaan multimedia pembelajaran ini bertujuan untuk mengatahui sejauh mana sekolah menerapakan dan mengetahui tentang digitalisasi di sekolah. Dengan mengenalkan media digital ke sekolah sejak jenjang sekolah dasar maka akan berdampak baik juga untuk perkembangan siswa dalam upaya pemanfaatan teknologi kedepannya. Metode penelitian yang di gunakan dalam penelitian ini adalah metode deskriptif kualitatif dengan Teknik wawancara dan kuisisoner yang di isi oleh siswa seputar pengguanaan media pembelajaran digital di sekolahnya. Dan faktor penyebab kurang efektifnya penggunaan multimedia digital di SDN nagasari 4 di pengaruhi oleh beberapa faktor eksternal dan internal .Kata Kunci: multimedia, media digital, pembelajaran